Neonatal health monitoring system with IOT application - O., Sheril Amira; H., Nor Asmira; Tengku Ibrahim, Tengku Nadzlin; Abd Wahab, Mohd Helmy; A.H., Omar; Ahmad, Muhammad Shukri; Ma'radzi, Ahmad Alabqari (JICETS, 2020)
The body temperature and heart rate are important parameters to monitor the neonatal situation. Neonatal need to be monitored closely in Neonatal Intensive Care Unit (NICU) to allow quick actions by physicians when any problems occur. The lack of systems that able to alert and indicates any warning condition of neonatal in NICU is one of the problems faced by most of the hospital. To reduce the complexity of the system at the NICU for monitoring the Neonatal condition from time to time, the health monitoring system using the Android app has been introduced. This system was introduced to improve the existing system to give alert and warning sign so that early precautions can be done. The project involves the LM35 temperature sensor and pulse sensor which is controlled by the Arduino Uno microcontroller with the help of instructions C / C ++, and Bluetooth networking system. This allows the user to monitor the baby's condition through applications that use Bluetooth networking system. Users must have the application that can be downloaded on Google Play. Furthermore, this system is not only applicable for the physicians but also for others to monitor the condition of Neonatal even though they are outside of the NICU. The neonatal condition can be checked by the LCD display.